MOTIVASI INDONESIA MENANDATANGANI NOTA KESEPAHAMAN DENGAN KUBA DI BIDANG OLAHRAGA TAHUN 2013 - Made Dwi Faranita; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research will explain about Indonesian‟s motivation when signing the Memorandum of Understanding with Cuba in Sporst on Mei 2013. As a great nation, Indonesia try to use all of the resources that it has to maintain its exsistention in the International sphere when the globalization is rapidly developed. Indonesia try to strengthening itself by increasing the sport achievements, one of them by having an agreement with Cuba in the Sports area. Cuba which has a good achivements history of baseball, boxing, volleyball, gymnastic, track and field are the reason for Indonesia to continue the agreement in Mei 2013. Previously, Indonesia had been signed the Memorandum Of Understanding with Cuba on Sport on Mei 2007 in Bali. Beside that, Indonesia and Cuba has a really good relations when the Che Guevara came to Indonesia and met Presiden Soekarno, after that Soekarno alternately visited Cuba and met the President, Fidel Castro and the government trying to keep this good relation.The writer collects data from the journal, books, online media, articles and The President‟s speech that related to the topic to analyze Indonesia‟s reason for signing the Mou and continuing the development. The theorical framework applied in this research are realism, soft power by Joseph Nye, and public diplomacy by Barry Sanders.The research shows Indonesia has its interest in signing the agreement with Cuba on Sport not only because Cuba has many achievements in their national sport such as boxing and baseball. Those interests are Indonesia try to enter the Cuba‟s domestic market, and keep the good relations in many objects.Keywords : Cuba, Indonesia, good relations ,memorandum of understanding, sports